2021
DOI: 10.14306/renhyd.25.3.1258
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de bebidas azucaradas, verduras y frutas en sujetos con alteración del metabolismo de la glucosa

Abstract: Introducción: Poco se conoce sobre los patrones de dieta de individuos con diabetes mellitus tipo 2 (DM2) en Perú. El objetivo del presente estudio fue determinar si existe asociación entre la alteración del metabolismo de la glucosa y ciertos patrones de dieta (consumo de bebidas azucaradas, verduras y frutas). Material y métodos: Análisis secundario de un estudio poblacional de tipo transversal realizado en Tumbes, en el norte del Perú. Las variables resultado fueron consumo de bebidas azucaradas, consumo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The finding of this study revealed that the magnitude of FV consumption among people with T2DM was 25.8% (with a 95% CI 20.9% to 31.5%). This finding is consistent with other research from other parts of the world, including Nigeria 17 and Brazil, 31 where FV intake rates were reported to be 27.0% and 23%, respectively. Additionally, other research conducted on both vegetable and fruit consumption revealed a rate of 25.5%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding of this study revealed that the magnitude of FV consumption among people with T2DM was 25.8% (with a 95% CI 20.9% to 31.5%). This finding is consistent with other research from other parts of the world, including Nigeria 17 and Brazil, 31 where FV intake rates were reported to be 27.0% and 23%, respectively. Additionally, other research conducted on both vegetable and fruit consumption revealed a rate of 25.5%.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, the study conducted in Delhi reported a rate of 33.3%, 7 while another study from Brazil, which focused on boys specifically, reported an even higher consumption rate of 36.7%. 31 However, these differences could be attributed to various factors, such as differences in sample size, sociodemographic status or methodological approaches employed across studies. It is also possible that food culture and availability could play an important role in shaping these dietary patterns.…”
Section: Discussionmentioning
confidence: 99%